Growth and yield of maize intercropped with vegetable amaranth as influenced by irrigation and fertilization methods - Anila, M. A.; Duraisamy, V. K.; Somasundaram, E. (Journal of Tropical Agriculture, 2019)
An experiment was conducted to study the effect of liquid organic manure application and limited irrigation on growth and yield characteristics of maize + vegetable amaranth at Tamil Nadu Agricultural University, Coimbatore during 2016 2018. The experiment was laid out in randomized block design with three replications. The treatments consisted of two irrigation methods and seven fertilizations. Drip irrigation and conventional furrow were the two irrigation methods. Humic acid 3 kg ha-1, fulvic acid 3 kg ha-1, vermiwash 5 per cent, jeevamiritham 5 per cent and their combinations, and inorganic fertilizers were the fertilization treatments. Drip irrigation recorded superiority in almost in all growth parameters and yield of crops. Among fertilization treatments, although inorganic fertilizer recorded significant influence on all the crop characteristics, it was comparable with humic acid 3 kg ha-1 + fulvic acid 3 kg ha-1. Among the organic manures humic acid and fulvic acid combination registered the highest yield in both years.